2017
DOI: 10.1016/s0140-6736(17)31191-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term management of moderate-to-severe atopic dermatitis with dupilumab and concomitant topical corticosteroids (LIBERTY AD CHRONOS): a 1-year, randomised, double-blinded, placebo-controlled, phase 3 trial

Abstract: Sanofi and Regeneron Pharmaceuticals Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

75
1,082
14
48

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 998 publications
(1,278 citation statements)
references
References 58 publications
75
1,082
14
48
Order By: Relevance
“…The overall rates of adverse effects were similar with dupilumab and placebo (88% vs. 84%, respectively) with 4% versus 5% classified as severe 26. Discontinuation due to adverse effects was higher among patients treated with placebo (8%) than with dupilumab (2%).…”
Section: About Dupilumabmentioning
confidence: 77%
See 3 more Smart Citations
“…The overall rates of adverse effects were similar with dupilumab and placebo (88% vs. 84%, respectively) with 4% versus 5% classified as severe 26. Discontinuation due to adverse effects was higher among patients treated with placebo (8%) than with dupilumab (2%).…”
Section: About Dupilumabmentioning
confidence: 77%
“…After 52 weeks of treatment, the incidence of herpetic skin infections was similar (7% with dupilumab vs. 8% with placebo); however, patients treated with dupilumab reported a higher incidence of localised herpes simplex infections (6% vs. 3%) 26. All herpes viral infections resolved by the end of the study 14…”
Section: About Dupilumabmentioning
confidence: 90%
See 2 more Smart Citations
“…The application of 300 mg dupilumab qw or q2w results in rapid improvement of clinical signs and symptoms; among patients with moderate to severe AD, up to 85% reach EASI-50, 44–51% reach EASI-75, and 30–36% achieve EASI-90 after 16 weeks, while the frequency of pruritus decreases by 40–60% [147, 148]. Dupilumab has a sustained effect over 1 year and a tolerable safety profile, with conjunctivitis as a noteworthy adverse event occurring in 14–19% of patients [149]. Recent published phase 2 studies have demonstrated that the monoclonal antibodies that block IL-13 (lebrikizu­mab and tralokinumab) are effective in patients with moderate to severe AD [150, 151].…”
Section: Therapeutic Management Of Admentioning
confidence: 99%